SAVING IGBO LANGUAGE FROM EXTINCTION: THE ROLE OF LIBRARIES AND LIBRARIANS IN IGBO LAND (NAU Journal of Library and Information Science, 2021)
This paper discussed Igbo language as an endangered indigenous language in Nigeria. The paper also highlighted the probable factors affecting the use of Igbo language in Nigeria. English language is the official language in Nigeria. It is the language of instruction in primary, secondary and tertiary education. Nigeria was a former British colony and part of our colonial heritage was the use of English language as our lingua franca. Even the Ibos who are the original owners of the language shy away from grooming their children at home with their mother tongue. The resultant effect is that these children grow into adulthood not speaking their mother tongue. Thus their language of communication both at home and in the school is English language. The paper equally discussed the role of libraries and librarians in the preservation of indigenous language. It suggested strategies through which libraries and librarians in Igbo land can preserve and promote Igbo language thereby saving it from possible extinction in future. Strategies suggested include collecting and documenting oral histories, provision of adequate information resources for Igbo studies, organizing lectures and programmes and deploying ICTs for promotion of Igbo language.
Keywords: Igbo Language; Indigenous Language; English Language; Libraries; Librarians; Igboland